2002
DOI: 10.1088/0022-3727/35/10/306
|View full text |Cite
|
Sign up to set email alerts
|

Transport coefficients including diffusion in a two-temperature argon plasma

Abstract: This paper presents the first application to an argon atmospheric plasma of a very recent derivation of a two-temperature (2T) transport properties theory, based on the Chapman-Enskog method expanded up to the fourth approximation, where only elastic processes are considered. The kinetic electron temperature Te is assumed to be different from that of heavy species Th, chemical equilibrium being achieved. This new theory, where electrons and heavy species are coupled, allows one to determine 2T diffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 45 publications
(76 reference statements)
6
88
1
Order By: Relevance
“…Recently, it has been shown by Rat et al [17,18] that due to the assumption of complete decoupling between electrons and heavy particles, values of diffusion coefficients used by Devoto in earlier computations were not consistent with mass conservation. Afterward, two-temperature properties including diffusion have been reported by Rat et al [19][20][21] for argon plasmas and by Aubreton et al [22] for argon-helium plasmas.…”
Section: Introductionmentioning
confidence: 89%
“…Recently, it has been shown by Rat et al [17,18] that due to the assumption of complete decoupling between electrons and heavy particles, values of diffusion coefficients used by Devoto in earlier computations were not consistent with mass conservation. Afterward, two-temperature properties including diffusion have been reported by Rat et al [19][20][21] for argon plasmas and by Aubreton et al [22] for argon-helium plasmas.…”
Section: Introductionmentioning
confidence: 89%
“…These authors analyzed systematically this problem and found possible causes related to the distribution of thermal conductivity and ionization energy. The reactive thermal conductivity due to ionization reactions should be assigned to the electron thermal conductivity [72,73]. The ionization energy should be accounted for in the electron rather than the heavy particle energy conservation [72].…”
Section: Plasma Column-modelling Assumptionsmentioning
confidence: 99%
“…and TADR matrices in Appendix A) are calculated using a finite difference approximation, e.g., The accurate calculation of nonequilibrium transport properties for a plasma following the Chapman-Enskog procedure [40,35] is computationally demanding, particularly within time- [41,29]. Figure 2 depicts the transport properties used.…”
Section: Materials Properties and Constitutive Relationsmentioning
confidence: 99%